Directions for Land Conservation Based on Determining the Erosion Hazard Index (EHI) Using the RUSLE Method in Sub-Watersheds Gunting, Jombang - Novita, Dian; Wijaya, Kemal; Sasongko, Purnomo Edi (Kadiri University - Faculty of Agriculture, 2024)
Land damage generally occurs due to erosion by the flow of rainwater on the soil surface. Erosion is closely related to the intensity of rainfall in an area and the slope of the land (slope). Soil erosion is an environmental problem which, if left unchecked in the long term, can reduce soil fertility. The Erosion Hazard Index (EHI) is used as a solution in controlling erosion at certain locations. The research was conducted in the Kali Gunting Sub-watershed in Wonosalam District, Jombang, East Java, in January 2021 to April 2023. The research locations covered several villages, namely: Galengdowo, Jarak, Wonomerto, Sambirejo, Wonosalam, Carangwulung, Panglungan, Wonokerto and Sumberrejo. Meanwhile, for soil sample analysis activities carried out at the Land Resources Laboratory I and II of the Faculty of Agriculture, East Java